Digital Challenges and Opportunities for ELT Teachers at Tertiary Level: A Post-COVID Review in Pakistan - Shazia Riaz Cheema; Dr. Mamona Yasmin Khan; Fatima Akbar (Indus Journal of Social Sciences, 2025)
This study explores the digital challenges and opportunities faced by English Language Teaching (ELT) teachers at the tertiary level in the post-COVID-19 era, aiming to enhance teaching practices, inform policymaking, and contribute to digital education. Using a mixed-methods approach, the research begins with a quantitative phase surveying more than two hundred ELT teachers about digital challenges and opportunities. This is followed by qualitative, in-depth interviews with five ELT teachers. Key challenges identified include disparities in technological infrastructure and access, gaps in digital literacy, maintaining student engagement, and adapting assessment methods to an online format. Conversely, opportunities include adopting innovative teaching methods, accessing global resources, emphasising continuous professional development, and leveraging the flexibility and accessibility of digital learning. The findings significantly affect stakeholders, educators, and institutions to improve teaching practices and student engagement. Policymakers can address systemic issues like the digital divide and promote digital literacy, and the need for professional development and innovative teaching methods is emphasised. The post-COVID era presents both challenges and opportunities for ELT teachers at the tertiary level. Addressing technological disparities, enhancing digital literacy, and developing effective engagement and assessment strategies are critical. By embracing digital innovations and resources, investing in professional development, and leveraging the flexibility of digital learning, these challenges can be transformed into opportunities, ultimately improving the quality and effectiveness of ELT.